Biomimetic dentistry - Suchetana Goswami (Wolters Kluwer Medknow Publications, 2018)
"Biomimetics" is the field of science that uses the natural system of synthesizing materials through biomimicry. This method can be widely used in dentistry for regeneration of dental structures and replacement of lost dental tissues. This is a review paper that states its scope, history, different fields of biomimetic dentistry, and its future conditions in India.